The Role of Land Deed Maker Officials in Making the Deed of Transfer of Land Rights and Registration of Transfer of Names During the Covid-19 Pandemic - Kholishotul Adibah; Dahniarti Hasana; Dini Amalia Fitri (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This research aims to know and analyze the role of land deed officials in making the deed of transfer of land rights and registration of transfer of names during the covid-19 pandemic at the Pekalongan City Land Office, to find out and analyze the legal consequences of making a deed of transfer of land rights that have been transferred, and to find out and analyze examples of a deed of transfer of land rights. This study uses a sociological juridical approach. This research specification uses descriptive analysis. The types and sources of data used in this study are primary data from interviews, while secondary data is obtained through library research. Research data collection is divided into 2 (two), namely primary data collection is done by interview and secondary data collection is done by collecting data contained in laws and regulations, books, articles and others. The data analysis method used in analyzing the data is qualitative analysis. The results of the study indicate that the role of PPAT is to carry out some of the tasks of the state in the land sector, as a public official who is authorized to make authentic deeds. Since the signing of the deed by the parties, PPAT as one of the implementing officials of land registration is obliged to submit the deed he made and register the name transfer at the local Land Office. Since the Covid-19 pandemic, the Pekalongan City Land Office has implemented 8 (eight) steps of the conventional or semi-online service process, this is done so that services continue to run in a conducive manner and prevent the spread of the covid-19 outbreak. Second, there is legal certainty and legal protection for new rights holders by making a deed of transfer of land rights which has been transferred to a certificate of land rights.